PENGARUH KEPERCAYAAN, KEGUNAAN DAN KEMUDAHAN TERHADAP MINAT MENGGUNAKAN SISTEM PEMBAYARAN E-WALLET GO-PAY PADA MASYARAKAT DI KECAMATAN ALALAK KABUPATEN BARITO KUALA - Ruslinda Agustina; Rara Gustiana; Muhammad Rizky Budiman (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2022)
The purpose of the study was to empirically prove the effect of trust, usability and convenience on interest in using the Go-Pay E-Wallet payment system in the community in Alalak District, Barito Kuala Regency. The method used is a survey method with a sample of 88 people as respondents. The test tool used with the help of the SPSS for windows release 20.0 program. The results showed that the trust variable affected the interest in using the Go-Pay e-wallet with a significant value of 0.038. The usability variable affects the interest in using the Go-Pay e-wallet with a significant value of 0.038. The convenience variable affects the interest in using the Go-Pay e-wallet with a significant value of 0.029.